Role of Human Papillomavirus in Hypoxia Microenvironment - Al-abadi, Akeel Abd Ali; Rwayeh Al-Asadi, Sahira Yaqoot; Mohsin, Fatima Taher; Khameiss, Ahmed Saadoon (Scientific Journal of Medical Research, 2024)
Background: Human papillomavirus is a double-stranded DNA and globally, there are approximately 300,000 deaths annually due to cervical cancer in women and 500,000 new infections with this virus. Toll-like receptor 4 (TLR4) is a receptor that triggers the innate immune response against the invading pathogen. Hypoxia in the solid tumor microenvironment participates in tumor development as a result of persistent infection. Materials and Methods: Samples of 48 tissue biopsies and Pap smear samples were taken from women’s cervix from Al-Mwani Teaching Hospital, Basrah Women and Children Hospital, and Al-Fayhaa Teaching Hospital. PCR was used to detect the presence of HPV in 89.6% of cases. Extraction of RNA and gene expression was performed for toll-like Mreceptor4, hypoxia-induced factor-1?, and B-actin. Results: The current study shows higher gene expression levels for all target genes in all positive samples compared to negative samples. The expression level of TLR4 of the positive samples was more than one times that of the negative samples. The gene expression of the hypoxia-induced factor-1? in positive samples was approximately 36-fold greater than in control samples. Conclusion: The current study indicates that there is a real increase in the level of gene expression for TLR4 and HIF-1? and that a higher level of expression of target genes in positive samples indicates a relationship with HPV infection compared to negative samples